If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 52y + -29 = 10 Reorder the terms: -29 + 52y = 10 Solving -29 + 52y = 10 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '29' to each side of the equation. -29 + 29 + 52y = 10 + 29 Combine like terms: -29 + 29 = 0 0 + 52y = 10 + 29 52y = 10 + 29 Combine like terms: 10 + 29 = 39 52y = 39 Divide each side by '52'. y = 0.75 Simplifying y = 0.75
| 5-(2x+5)=4+4(x+2) | | 12+5n=32 | | x^2+10x-4=10 | | 2q-4=26 | | 115=5t | | -9v-9=-27 | | x^2-13+6x=0 | | -15+10y=25 | | t^2-6t+10=0 | | -30p-2=58 | | 9(5x-2)=32 | | x*12-213=x*4-5 | | p^2-4p-1=0 | | -30-2=58 | | x^2=6x-13 | | 47-7x=2x+19 | | 14+14p=21 | | 7n+(5n+15)=32 | | 140-5x=6x+19 | | 4lnx+lnx^3-lny=lna | | .2x-.5=.5-.2(2x-13) | | 6x+6=126-6x | | Q*3=-4 | | x^2-8x-48=0 | | 1+6x=51+x | | n^2-n=2 | | x*x-4x+3=0 | | 4x-1=11-2 | | x^2-5x=2x+3 | | 4x^2-15x+17=-2x+8 | | 12h+9=-2h-11 | | x^2-14-4=0 |